ULOGA MIKRO-RNA-346 U PROGRESIJI RAKA PROSTATE: KLINIČKI ZNAČAJ I POTENCIJAL KOJI IMA KAO BIOMARKER - Wang, Lei; Wang, Yanqing; Tian, Li; Wang, Zhengwei; Liu, Xiaoqiang; Chen, Guangzhou (Journal of Medical Biochemistry, 2025)
Objective: The aim of this study was to analyze the expression changes and clinical significance of microRNA-346 (MiRNA-346) in PCa genesis, development and hormone resistance transformation.Method: Data of the middle-aged and elderly male patients who were treated in Tengzhou Central People’s Hospital from January 2017 to December 2023 were collected. The tissues and corresponding preoperative serum of 128 patients with newly diagnosed PCa and 130 patients with benign prostatic hyperplasia (BPH), 120 patients with hormone-sensitive PCa (HSPC), 116 patients with castration-resistant PCa (CRPC), and 150 healthy males of the same age who underwent physical examination in the physical examination center of our hospital were collected. Quantitative real-time polymerase chain reaction was used to detect the relative expression of miRNA-346 in the tissues and serum of the subjects. GraphPad Prism statistical analysis software was utilized to analyze the expression changes of miRNA-346 in the occurrence and progression of PCa and its correlation with clinical and pathological features.Result: The expression of miRNA-346 was significantly lower in PCa patients than in BPH patients and healthy population (P